2001
DOI: 10.1046/j.1460-9592.2001.t01-1-00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restoration of AV Synchrony on Stroke Volume, Exercise Capacity, and Quality‐of‐Life: Can We Predict the Beneficial Effect of a Pacemaker Upgrade?

Abstract: The aim of this study was to assess to what extent patients with VVIR pacemakers and without overt symptoms of a pacemaker syndrome benefit from a pacemaker upgrade, and if a preoperative noninvasive measurement of the change in stroke volume (SV) could predict the effect of a pacemaker upgrade. The study group consisted of 20 (12 women, 8 men) VVIR patients with a mean age of 60 years. The indication for the first implantation was AV block in 13 patients and SSS in 7. The mean time of a ventricular pacing was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…In one study, 16 patients with VVIR pacemakers were given atrial leads and randomized to ventricular demand pacing or physiologic pacing; perceived well-being and exercise capacity were improved during physiologic pacing (14). This finding was confirmed in 2001 in a similar study of 20 patients who had an atrial lead placed at the time of generator replacement; stroke volume and exercise capacity were increased in all individuals, and those with sick sinus syndrome had an improvement in quality of life (15). Finally, it is also possible that the greater percentage of beats paced (which was predictive of the development of pacemaker syndrome in the current study) was lower in those studies that reported low frequencies of pacemaker syndrome.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In one study, 16 patients with VVIR pacemakers were given atrial leads and randomized to ventricular demand pacing or physiologic pacing; perceived well-being and exercise capacity were improved during physiologic pacing (14). This finding was confirmed in 2001 in a similar study of 20 patients who had an atrial lead placed at the time of generator replacement; stroke volume and exercise capacity were increased in all individuals, and those with sick sinus syndrome had an improvement in quality of life (15). Finally, it is also possible that the greater percentage of beats paced (which was predictive of the development of pacemaker syndrome in the current study) was lower in those studies that reported low frequencies of pacemaker syndrome.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that subclinical pacemaker syndrome may be present and undiagnosed in studies that require surgical revision to upgrade patients to a physiologic-based system (14,15). In one study, 16 patients with VVIR pacemakers were given atrial leads and randomized to ventricular demand pacing or physiologic pacing; perceived well-being and exercise capacity were improved during physiologic pacing (14).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the prolonged AV delay during slow pathway conduction of atrial tachycardia, each atrial contraction was likely simultaneous with the preceding ventricular systole. Contraction of the atrium against closed AV valves may lead to reduced cardiac output due to loss of atrial contribution to ventricular filling, and to baroreflex‐mediated autonomic changes 7–10 …”
Section: Discussionmentioning
confidence: 99%
“…To prevent these malfunctions, the devices of the patients submitted to physical rehabilitation have to be reprogrammed accordingly after establishing their maximum heart rate during the exercise test [18,19]. Several clinical studies have shown that the programming mode of the cardiac pacemakers can also have a significant influence on the patients exercise capacity, a crucial element of any physical rehabilitation program (table 3) [20,21,22]. The most frequently implanted pacemakers are singlechamber (VVI -right ventricular pacing) and dualchamber (DDD -right atrial and right ventricular pacing), with or without the rate response function activated.…”
Section: Specific Complications Related To Intracardiac Devicesmentioning
confidence: 99%